Family violence and elder abuse — an insight on concepts and practices for caregivers - Cardoso, João Casqueira (2010)
Este artigo visa clarificar os conceitos de violência familiar e violência contra o idoso. Ambos os fenómenos são de especial interesse para a comunidade académica, bem como para os profissionais de saúde em geral, e para os cuidadores e gestores em saúde em particular. A perspectiva deste texto é uma perspectiva comparada, permitindo uma visão global sobre a violência familiar e a violência contra o idoso na europa do sul e nos estados unidos. o artigo propõe igualmente uma lista organizada de práticas para prevenir e melhor administrar as decisões em caso de violência contra o idoso. This article intends to clarify the concepts of family violence and elder abuse. both phenomena are of interest for the academic community, as well as for the health professionals in general, and for the health caregivers and health managers in particular. the text is written in a comparative perspective, allowing for a global vision on family violence and elder violence in southern europe and in the united states. it also proposes a list of organized practices in order to prevent violence and to better manage decisions in case of elder violence.